2013
DOI: 10.1039/c3ob41546e
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-catalyzed reductive homocoupling of N′-tosyl arylhydrazines

Abstract: A novel procedure for the preparation of biaryl compounds by Pd-catalyzed homocoupling of N'-tosyl arylhydrazine has been described. N'-Tosyl arylhydrazine, as a readily available and stable coupling partner, demonstrated its generality in the homocoupling reactions. The scope of the reaction and possible mechanism have also been investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…To support the radical mechanism, we carried out the radical trapping experiment by using 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO) under optimized conditions (Scheme ), this afforded TEMPO adduct 1-(2,2,6,6-tetramethylpiperidinyloxy)-benzene ( 6 ). On the basis of our experimental results and previous literature, ,, we outlined a radical-mediated reaction mechanism as shown in Scheme . After formation of the free phenylhydrazine from its hydrochloride salt ( 1 ) in the presence of base, it undergoes single electron transfer in the presence of oxygen to form phenylhydrazine cation radical intermediate, which upon simultaneous loss of H + in the presence of base leads to phenylhydrazyl radical [ A ].…”
mentioning
confidence: 70%
“…To support the radical mechanism, we carried out the radical trapping experiment by using 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO) under optimized conditions (Scheme ), this afforded TEMPO adduct 1-(2,2,6,6-tetramethylpiperidinyloxy)-benzene ( 6 ). On the basis of our experimental results and previous literature, ,, we outlined a radical-mediated reaction mechanism as shown in Scheme . After formation of the free phenylhydrazine from its hydrochloride salt ( 1 ) in the presence of base, it undergoes single electron transfer in the presence of oxygen to form phenylhydrazine cation radical intermediate, which upon simultaneous loss of H + in the presence of base leads to phenylhydrazyl radical [ A ].…”
mentioning
confidence: 70%
“…In cross‐coupling arylation. Recent advances in the coupling reactions of arylhydrazine, which is utilized as an effective arylation partner in oxidative radical arylation and Pd‐catalyzed cross‐coupling (Heck‐type, Suzuki‐type, addition, homocoupling, etc …”
Section: Introductionmentioning
confidence: 99%
“…31 Our previous study revealed that N′-tosyl arylhydrazine was another efficient coupling partner. 32,33 In an attempt to explore a more stable coupling reagent, we noticed that N′-aryl hydrazides can be cleaved under mild oxidative conditions to afford aromatic alkenes, 34 which implied that N′-aryl hydrazides might also act as aryl donors for some coupling reactions. Herein, we reported the first copper(II)-catalyzed homo-coupling reaction of N′-aryl acylhydrazines for the synthesis of symmetrical N′,N′diaryl acylhydrazines.…”
Section: Introductionmentioning
confidence: 99%